2014
DOI: 10.3109/07420528.2013.867864
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of the Korean version of Morningness–Eveningness Questionnaire in adults aged 20–39 years

Abstract: Morningness-Eveningness (ME) can be defined by the difference in individual diurnal preference observed from general behavioral patterns including sleep habits. The Horne & Östberg Morningness-Eveningness Questionnaire (MEQ) has been used for classifying ME types. We examined the reliability of a Korean version of the MEQ (Korean MEQ) and verified its validity by comparing responses on the Korean MEQ to objectively-recorded sleep-wake rhythms. After translating and back translating the MEQ from English into Ko… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
50
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 44 publications
7
50
0
1
Order By: Relevance
“…Daily training would be effective to promote the circadian amplitude, and this masking effect would diminish the difference between chronotypes. The data of the circadian rhythm of activity levels demonstrated that there was a clear difference between ''larks'' and ''owls''; these results are in line with other studies that showed biological differences among chronotypes: Lee et al (2014), using actigraphy, argued that the mean activity acrophase of E-types was nearly 2 h later in the morning than M-types. Moreover, Gupta & Pati (1994) demonstrated that M-types have an earlier circadian oral temperature acrophase than E-types, and this difference was approximately 2 h (Baehr et al, 2000).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Daily training would be effective to promote the circadian amplitude, and this masking effect would diminish the difference between chronotypes. The data of the circadian rhythm of activity levels demonstrated that there was a clear difference between ''larks'' and ''owls''; these results are in line with other studies that showed biological differences among chronotypes: Lee et al (2014), using actigraphy, argued that the mean activity acrophase of E-types was nearly 2 h later in the morning than M-types. Moreover, Gupta & Pati (1994) demonstrated that M-types have an earlier circadian oral temperature acrophase than E-types, and this difference was approximately 2 h (Baehr et al, 2000).…”
Section: Discussionsupporting
confidence: 88%
“…The results regarding sleep timing have shown that E-types generally go to bed and wake-up significantly later than M-types on both work and free days; therefore, eveningness is associated with a later bedtime and wake-up time and a shorter time in bed during the week (Giannotti et al, 2002;Kabrita et al, 2014;Lee et al, 2014;Roepke & Duffy, 2010). No data were reported regarding sleep quality.…”
Section: Introductionmentioning
confidence: 94%
“…The reliability of the internal consistency and the test–retest, as well as the external validity of the MEQ, have been reported in previous studies [26,27]. The total range for the MEQ score is 16–86, and all of the questions refer to the participant’s personal sleep habits.…”
Section: Methodsmentioning
confidence: 58%
“…The Korean version of Morningness-Eveningness Questionnaire (MEQ-K) [19], the Korean version of Epworth Sleepiness Scale (KESS) [20], and Pittsburgh Sleep Quality Index (PSQI) [21] translated into Korean were administered to 2 011 recruited subjects. Buccal DNA samples were obtained from 400 subjects, who agreed to donate a buccal swab for the genetic study.…”
Section: Subjectsmentioning
confidence: 99%